(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2017)
The references of studies about the magnetic field effect on prevention of asphalt, resin, and paraffin and salt deposits formation in the oil are described in the article. The effect of constant magnetic fields on the well production is currently one of the most interesting, leading to an increase in the overhaul period of the well. At the same time, this method is debatable, sometimes leading to ambiguous and contradictory results. In many cases, the nature of such effect is not properly studied. Often, according to some researchers, effect is discovered, whereas its intensity, on the basis of physical considerations, is clearly inadequate for the production of any useful effect. This refers to the type of magnetic effects, that is based on the principle of protection consisting in a sharp increase in 1000-100000 times the number of paraffins crystals nucleus by the action of static magnetic fields of topology and tension in the natural trace units - rod-shaped mineral oxides / hydroxides of iron are water, oil and gas production in the flow of production wells. Keywords: development of oil fields, asphalt, paraffins, resins, sediments, asphaltene deposits, salt deposits, the magnetic field, the magnetic anti-paraffin device.